Yussibnosh toughened up by hardship - Wong, Dennis (New Straits Times, 2014)
AS a boy, Barisan Nasional (BN) candidate for the Balingian by-election, Yussibnosh Balo, climbed coconut trees and sold corn by the roadside. The son of a sago tree cutter would do odd jobs during weekends to make ends meet in Tellian here and walked 5km to get to his school.